The Effects of the Anglo-Siamese Treaty 1909 on Northern Malay States - Arifin, Azmi; Hussain, Nik Haslinda Nik; Rosdi, Mohamad Roslaily (European Publisher, 2019)
This study examines the effects of the Anglo-Siamese Treaty of 1909 on the northern Malay States, particularly Kelantan and Terengganu. The objective of this study is to analyse the primary effects of the Treaty of 1909 on the fate of the Malay states, particularly those that had been put under the British control. This study uses a qualitative research method based on the examination of the primary and secondary sources. The results of this study indicated that the Rulers of the Malay states, especially Kelantan and Terengganu, had reacted negatively to the treaty. This study also explain the existence of Malay opposition to the Siamese and British, which was translated through the anti-British uprising in Kelantan and Terengganu in 1915 and 1928 respectively, as well as prolonged resistance of the Malays from the northern Malay provinces that were still under the control of the Siamese/Thais up to this day. This study proves that the policy of British imperialism could not escape its direct and indirect negative impact on the Malay States.